Ekstraksi Pigmen Klorofil Total Pada Mikroalga Dunaliella sp. Yang Telah diberi Perlakuan Timbal Asetat - Oscar M Lamohamad; Kurniati Kemer; Desy M H Mantiri; Ester Angkow; James Paulus; Adnan S Wantasen (Sam Ratulangi University, 2021)
Heavy metals such as lead are compounds that can cause toxic effects if they enter the body of living things. Dunaliella sp. is one of the marine organisms that is susceptible to changes or ecological pressure so that it is the main target of being exposed to pollutants such as heavy metals and so on, so it is necessary to conduct research to determine how the effect of lead acetate compounds on the growth and total chlorophyll content of Dunaliella micro algae. sp. The results of this study indicate that the growth of Dunaliella sp microalgae on the control culture media and the lead treatment media has a very different growth, the control media has normal growth, while the total chlorophyll content of the 14th day in the control media is 80.49 µg / ml. 30 ppm 54.79 µg / ml, 50 ppm 50.02 µg / ml and 100 ppm 9.13 µg / ml. While the total chlorophyll content of the 30th day in the control media was 34.99 µg / ml, 30 ppm 44.657 µg / ml, 50 ppm 26.136 µg / ml and 100 ppm 5.58 µg / ml.Keywords : Microalga, Dunaliella sp, kcorophyll, lead ecetate